Training And Developing Physician-Scientist Careers To Enhance Medical Research In Ghana. - Tette , E.M.A.; Lawson, H.J.O.; Koram, K.; Sampane-Donkor, E.; Tette, A.R.A.; Quarshie, A.; Hodgson, A. (Postgraduate Medical Journal of Ghana, 2024)
A physician-scientist is a medical doctor who combines clinical practice with research. They often work in academic medical centers, research institutions, or hospitals, where they split their time between treating patients and conducting research to advance medical knowledge, develop new treatments, and improve public health. Their work is well recognized as they are reported to constitute 37% of Nobel Prize winners in Physiology or Medicine, and several prize winners in Chemistry. However, regardless of how inherently fulfilling this may be, in Ghana and many other regions of the world, increasingly fewer doctors aspire to become physician-scientists. Currently, there is a lack of clarity regarding the path to becoming a physician scientist in Ghana and other African nations. So, for the young doctor of today who wishes to embark on a research career, there are more questions than answers. The authors emphasize the need for structured programs, early commitment, and resource allocation to nurture the next generation of physician-scientists. They also examine the potential of integrating research-focused training into existing medical programs and the role of various stakeholders, such as universities and the Ministry of Health, in supporting these initiatives. The authors call for innovative approaches and strategic planning to enhance the capacity of Ghanaian doctors to pursue careers in medical research, ultimately contributing to global scientific advancement and improving healthcare in low and middle-income countries. They conclude that more needs to be done to develop more physician-scientists.
Research Article
Keywords: Physician-Scientist Careers; Medical Research; Ghana